Pragmatic Analysis of Energy Conservation in MANETs - Sharma, Bobby (International Journal of Computer Sciences and Engineering, 2015)
Mobile ad hoc network (MANETs) is a collection of mobile nodes in which all the nodes are connected via wireless link. These are self configured networks. MANETs contains several characteristics. Because of these intrinsic properties, MANETs becomes special amongst the users. Nodes in MANETs perform in open media that permits the network to work without preinstalled infrastructure. These give tremendous flexibilities to MANETs. Since the nodes in MANETs are wireless and mobile at the same time, so these are dependent on battery or any exhaustible power device. All activities including computation, packet forwarding etc. are always associated with energy conservation. Due to lack of sufficient battery backup, nodes may show vulnerabilities. In this paper, it is approached to discuss the different factors concerning the energy consumption. Also simulation results are shown using NS 2 simulator.